(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Composting is essential & cost-effective way to recycle organic waste. A variety of microorganisms are involved in composting process. Composting has many advantages: it improves manure management, creates a potentially saleable product, mends land application, destroys weed seeds & pathogens due to higher temperature in pile of compost, reduces danger of various pollution issues, & is an excellent soil conditioner. It is procedure that involves biological disintegration of waste which is organic under a variety of regulated settings. To accomplish co-benefits of value-added & environmentally friendly goals while fostering circular economy in accordance with quality of compost evaluation, a thorough knowledge of fate of nutrients & carbon in composting procedure is required. This article is analysis that aims for filing gaps in human understanding of composting process. To begin, a comprehensive screening search & descriptive analysis of composting models including fates of carbon (C), nitrogen (N), phosphorus (P), & potassium (K) during previous decade were performed.